Assessment of Serum Cytokines and Oxidative Stress Markers in Elite Athletes Reveals Unique Profiles Associated With Different Sport Disciplines - Sohail, Muhammad U.; Al-Mansoori, Layla; Al-Jaber, Hend; Georgakopoulos, Costas; Donati, Francesco; Botrè, Francesco; Sellami, Maha; Elrayess, Mohamed A. (Frontiers in Physiology, 2020)
Objectives: Circulating cytokines and oxidative stress markers vary in response to different exercise regimens. This study aims to compare the immune-inflammatory and oxidative stress profiles of elite athletes from different sport disciplines as potential biomarkers of muscle damage, and cardiovascular demand. Methods: Serum samples from 88 consented elite male athletes from different sports disciplines (aquatics, n=11, athletics, n=22, cycling, n=19, football, n=28 and weightlifting, n=8) collected at the anti-doping lab in Italy were screened for 38 cytokines and oxidative stress markers. Comparisons were made between different level of power, cardiovascular demand (CD) and endurance, as well as among the sport types. Results: The anti-inflammatory interleukin (IL)-10 was higher (p=0.04) in moderate power compared with the high power group. Conversely, superoxide dismutase (SOD; p=0.001) and malondialdehyde (MDA; p=0.007) levels were greater in the higher power groups compared with the lower power counterpart. Among athletes who belong to different CD ranks, IL-1β and monocyte chemoattractant protein-1(MCP1) levels were higher (p=0.03) in the low CD-rank group compared with high CD counterpart, whereas, SOD levels were higher (p=0.001) in high and moderate CD-rank groups compared to low counterpart. For endurance groups, IL-10 and macrophage inflammatory protein (MIP)-1beta were increased (p=0.03) in low/moderate endurance compared with the high endurance group. Finally, MIP1-beta, SOD and catalase varied significantly among the sports groups.